2018
DOI: 10.3389/fimmu.2018.02982
|View full text |Cite
|
Sign up to set email alerts
|

HMGN1 and R848 Synergistically Activate Dendritic Cells Using Multiple Signaling Pathways

Abstract: High mobility group nucleosome-binding protein 1 (HMGN1 or N1) is a Th1-polarizing alarmin, but alone is insufficient to induce antitumor immunity. We previously showed that combination of N1 and R848, a synthetic TLR7/8 agonist, synergistically activates dendritic cells (DCs) and induces therapeutic antitumor immunity, however, it remained unclear how N1 and R848 synergistically activate DCs. Here, we show that co-stimulation with N1 and R848 of human monocyte-derived DCs (MoDCs) markedly upregulated DC's sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
1
28
1
Order By: Relevance
“…Absence of tumor specific immune response in Hmgn1 −/− mice and increased anti-tumor immune response, when vaccinated mice with DNA vector overexpressing HMGN1, provide further support the role of HMGN proteins in regulating immune cell function and response [88]. Intratumor delivery of HMGN1 and TLT7/8 synthetic agonist R848, along with a checkpoint inhibitor Cytoxan synergistically activates dendritic cells for optimal Th1 response and eradicated large established CT26 tumors in mice [89,90]. Moreover, low doses of HMGN1 with anti-CD4 depleting antibody promoted the expansion of anti-tumor CD8 T cells by rescuing them from exhaustion [91].…”
Section: Immune Functionsmentioning
confidence: 78%
“…Absence of tumor specific immune response in Hmgn1 −/− mice and increased anti-tumor immune response, when vaccinated mice with DNA vector overexpressing HMGN1, provide further support the role of HMGN proteins in regulating immune cell function and response [88]. Intratumor delivery of HMGN1 and TLT7/8 synthetic agonist R848, along with a checkpoint inhibitor Cytoxan synergistically activates dendritic cells for optimal Th1 response and eradicated large established CT26 tumors in mice [89,90]. Moreover, low doses of HMGN1 with anti-CD4 depleting antibody promoted the expansion of anti-tumor CD8 T cells by rescuing them from exhaustion [91].…”
Section: Immune Functionsmentioning
confidence: 78%
“…In fact, the abundance of infiltrating leukocytes is an independent risk factor for the pathologic progression of acute myocarditis into long-term cardiac dysfunction [ 30 ]. The majority of the accumulated leukocytes in inflamed heart tissue of CV-infected mice are CD11b + monocytes and macrophages [ 35 , 40 ], with infiltration of these immune cells being driven by respective chemotactic cytokines [ 2 ]. Others and we demonstrated that particularly those infiltrating myeloid cells contribute to acute and chronic functional impairment in inflammatory heart disease [ 24 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies from Dr. Oppenheim's group have shown how HMGN1 contributes to the generation of antitumor immunity and has therefore drawn interest as a potential target for antitumor therapy (71). They made the observation that synergistic effect of R848 (TLR7/8 agonist) along with HMGN1 (TLR4 agonist) leads to augmented IL-12 responses and phenotypic maturation of mouse bone marrow derived dendritic cells (BMDCs) (72). This led to the development of a therapeutic vaccine (TheraVac) combining HMGN1 and R848 plus a checkpoint inhibitor (Cytoxan), which is effective on large tumors in mice without use of exogenous tumor-associated antigen(s) (73).…”
Section: Vaccines For Non-infectious Indicationsmentioning
confidence: 99%